Cellulolytic activity in the rumen of lambs fed a high concentrate diet is not affected by the removal of protozoa - Yáñez Ruiz D.R.; Martín-García A.I.; Hart K.J.; Molina Alcaide E.; Newbold C.J. (Nutritional and foraging ecology of sheep and goats, 2009)
Removing protozoa from the rumen may increase animal productivity. However, it is also known that protozoa play an important role in fibre degradation in the rumen. The aim of this work was to study the cellulolytic activity and microbial numbers in the rumen of faunated and protozoa free animals fed a high concentrate diet. Ten crossbred lambs were used. They were taken from the ewes within the first 24 h after birth and kept isolated from adult animals and bottle fed during 6 weeks. Once weaned five of them were given orally 10 ml of rumen fluid collected from adult sheep rumen at the slaughter house (faunated group, F). The other five lambs were given 10 ml of rumen fluid that had been previously centrifuged at 1000 g for 10 min and then frozen and thawed (protozoa free group, PF). Both groups were fed a mix of concentrate supplement and grass hay (60:40) for 5 months. Methane emissions were measured individually over a 3 day period. After slaughter, samples from the rumen were collected to study cellulose degradation using the most-probable number procedure. The numbers of Fibrobacter succinogenes, Ruminococcus flavefaciens, Ruminoccus albus and total fungi were quantified by real time PCR using specific primers and DNA isolated from rumen samples (200 mg). PF lambs produced 26% less methane than F lambs. No differences in the cellulolytic numbers were observed between groups. Real time PCR showed no differences in F. succinogenes and other cellulolytic bacteria numbers between F and PF animals. Our results show that in animals fed high concentrate diets the removal of protozoa from the rumen does not seem to affect cellulolytic activity.
12. Seminar on: Nutritional and Foraging Ecology of Sheep and Goats, 2007/10/11-13, Thessaloniki (Greece)